Information Overload and the Decision-Making Process of Consumers in Today’s World - Dr. Rakesh Kumar (Innovative Research Thoughts, 2017)
There is an excess of information available to customers in the modern digital era from a variety of sources, such as social media, internet reviews, ads, and product suggestions. Consumers face formidable obstacles in making educated decisions due to information overload, which forces them to sift through overwhelming volumes of data. the effects of information overload on consumers' decision-making process, namely how an abundance of data can cause analytical paralysis, decision fatigue, and, in the end, less-than-ideal choices. the impact of heuristics and cognitive biases on consumer decision-making when confronted with an abundance of information, drawing attention to the propensity to employ simplification and shortcut techniques as coping mechanisms. In addition, we go into tactics that customers may use to handle an excess of information and make better choices, like establishing criteria for making decisions, categorising information sources, and looking for reliable sources. how technology and recommendation systems powered by artificial intelligence may help with information filtering and personalisation to lessen overload and make decisions easier. Consumers may successfully traverse the intricacies of today's information-rich world and make better, more fulfilling choices if they are aware of the difficulties associated with information overload and have good coping mechanisms. the effects of information overload on consumers' decision-making processes and provide actionable advice for dealing with this modern phenomenon.